PELATIHAN MENGGUNAKAN SOFTWARE MATHCAD BAGI MAHASISWA PROGRAM STUDI TEKNIK MESIN UNIVERSITAS MUHAMMADIYAH PONTIANAK - Gunarto . (Jurnal Buletin Al-Ribaath, 2018)
The purpose of this community service was to train students of Mechanical Engineering Program University of Muhammadiyah Pontianak in using MATHCAD software. This training aims to support the courses of Basic Calculus, Advanced Calculus, Basic Engineering Mathematics,  Advanced Engineering Mathematics and to improve the ability of Mechanical Engineering students about software MATHCAD. The program included preparation, training, and reporting. As the program ended, understanding of training participants in using this software is able to apply independently by direct practice with MATHCAD software properly. Keywords: engineering, MATHCAD, mathematics, software, training